Pulse density modulation for maximum efficiency point tracking of wireless power transfer systems - Li, Hongchang (2019)
Maximum efficiency point tracking (MEPT) control has been adopted in state-of-the-art wireless power transfer (WPT) systems to meet the power demands with the highest efficiency against coupling and load variations. Conventional MEPT implementations use dc/dc converters on both transmitting and receiving sides to regulate the output voltage and maximize the system efficiency at the expense of increased overall complexity and power losses on the dc/dc converters. Other implementations use phase-shift control or on-off control of the transmitting side inverter and the receiving side active rectifier instead of dc/dc converters but cause new problems, e.g., hard switching, low average efficiency, and large dc voltage ripples. This paper proposes a pulse density modulation (PDM) based implementation for MEPT to eliminate all the mentioned disadvantages of existing implementations. Delta-sigma modulators are used as an example to realize the PDM. A dual-side soft switching technique is proposed for the PDM. The ripple factor of the output voltage with PDM is derived. A 50 W WPT system is built to validate the proposed method. The system efficiency is maintained higher than 70% for various load resistances when the power transfer distance is 0.5 m, which is 1.67 times the diameter of the coils.